The Role of Al and Big Data in Detecting Illegal Finance, Sharia Violations, and Cybercrime in the Digital Society Era Society 5.0 - Tuti’ Nadhifah; Heni Risnawati; Dian Rosita (Pandecta Research Law Journal, 2026)
Technological developments in the Society 5.0 era have driven massive digital transformation in various sectors, including in the financial system and law enforcement. In this context, artificial intelligence (AI) and Big Data have a strategic role in detecting illegal financial activities, violations of sharia principles in transactions, and increasingly complex cybercrime. This article discusses how AI and Big Data are used as real-time detection and prevention tools for transaction anomalies, money laundering patterns, and online fraud practices. In addition, this study highlights the regulatory and ethical challenges in the application of this technology, especially in ensuring compliance with sharia principles and personal data protection. With a normative qualitative method and a multidisciplinary approach, this paper offers a legal and technological perspective in responding to the dynamics of digital crime and the importance of collaboration between regulators, financial institutions, and technology providers to create a safe and equitable digital ecosystem. The findings in this article are expected to be strategic input in formulating legal policies and strengthening technology-based supervision systems in the digital era.